Learning better together? A scoping review of in-person interprofessional undergraduate simulation - Brona Joyce; Davina Carr; Alison Smart; Dakota Armour; Gerard J. Gormley (Advances in Simulation)
Abstract Background Given the increasing complexity of contemporary clinical practice, there has never been a more important time to provide interprofessional educational (IPE) activities across the learning continuum to develop collaborative practice. From the outset of health professional training, it is crucial that students not only develop their own professional skills but also gain an awareness of the capabilities of other healthcare professionals and how best to work collaboratively. Despite simulation being a common teaching modality in many undergraduate curricula, little is known about the range of interprofessional activities within these settings. Therefore, this study aims to address the following research question: What is known about undergraduate in-person (IP) simulation-based education (SBE)? Methods We conducted a scoping literature review, adhering to the PRISMA-ScR extension guidelines, and used the Arksey and O’Malley framework. Our search covered three electronic databases: Web of Science (WOS), MEDLINE, and Embase. We utilised Covidence systematic review software to assist in screening articles. To support data charting, we developed a data extraction tool and employed both qualitative and quantitative techniques through numerical and thematic analysis to ensure a comprehensive representation of our data. Results A total of 97 studies were included, with most publications originating from the USA, UK, and Australia. Two main themes emerged regarding the impact of IP SBE at an individual level: confidence and role identification. Several themes related to the impact on teams included knowledge of other professional roles/values, communication, and teamwork. The studies identified various barriers and enablers to simulation, particularly logistical barriers and financial challenges associated with complex technologically enabled simulation. Faculty collaboration and resources were reported as primary enablers in facilitating the delivery of simulation activities. Conclusions The impact of IP-SBE on learners and interprofessional teams is predominantly positive, with reported benefits including increased confidence, enhanced role identification, and improved communication and teamwork skills. However, challenges such as logistical barriers and resource constraints highlight the need for collaborative faculty efforts and adequate infrastructure to support IP-SBE implementation. Despite the growing interest in IP-SBE, there remains a notable lack of standardised reporting on simulation design and debriefing processes in both teaching practice and research.